Household Cooking Fuel Choice and Adoption of Improved Cookstoves in Developing Countries : A Review - Malla, Sunil (World Bank, Washington, DC, 2014)
Improving access to affordable and reliable energy services for cooking is essential for developing countries in reducing adverse human health and environmental impacts hitherto caused by burning of traditional biomass. This paper reviews empirical studies that analyze choices of fuel and adoption of improved stoves for cooking in countries where biomass is still the predominant cooking fuel. The review highlights the wide range of factors that influence households cooking fuel choices and adoption of improved stoves, including socioeconomic (access and availability, collection costs and fuel prices, household income, education and awareness), behavioral (food tastes, lifestyle), and cultural and external factors (indoor air pollution, government policies). The paper also summarizes the evidence on the significant adverse health impacts from exposure to indoor smoke, especially among women and young children. In low-income households, perceived health benefits of adopting improved stoves and financial benefits from fuel savings tend to be outweighed by the costs of improved stoves, even after accounting for the opportunity cost of time spent collecting biomass fuel. The paper identifies knowledge and evidence gaps on the success of policies and programs designed to scale up the adoption of improved cookstoves.